A Case Series of Severe Hospitalized COVID-19 Patients Treated with Tocilizumab and Glucocorticoids: A Report from Saudi Arabian Hospital - Salma AlBahrani; Jaffar A. Al-Tawfiq; Abdulaziz R. Alshaer; Amal Shilash; Khalid Alswefy; Razan Salamah Al-Zayer; Amr Mohamed Abouelela (Springer, 2021)
Background: The clinical spectrum of COVID-19 is variable and ranges from asymptomatic, mildly symptomatic, moderately severe and severe disease. A small proportion might develop severe disease and may have cytokine storm. One of the therapeutic options to treat such cases is Tocilizumab (TCZ). In this study, we present cases of severe COVID-19 treated with TCZ and glucocorticoids and discuss the treatment responses. Methods: This is a retrospective observational study of severe COVID-19 cases treated with TCZ and glucocorticoids. The case series examined the characteristics and outcome of those patients. Results: This study included 40 Severe Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) confirmed patients who received TCZ and glucocorticoids. The mean age of the included patients was 57.55 (±Standard deviation 12.86) years. There were 34 (85%) males, 19 (47.5%) were obese (BMI >30), 13 (32.5%) over weight, and five (12.5%) normal weight. The mean days from positive SARS-CoV-2 polymerase chain reaction (PCR) test to admission was 1.641 (±3.2) days. Of the patients, 18 (45%) had diabetes mellitus, 14 (35%) had hypertension. The mean days from hospital admission to ICU was 1.8 (±2.6), 20 (50%) required mechanical ventilation, 39 (97.5%) had received prone position, seven (17.5%) had renal replacement therapy, 13 (32.5%) required inotropes, four (10%) had plasmapheresis, one (2.5%) had intravenous immunoglobulin, all patients received steroid therapy, and the majority 31 (77.5%) did not receive any anti-viral therapy. Of all the patients, six (15%) died, 28 (70%) were discharged and six (15%) were still in hospital. Conclusion: The overall mortality rate was lower than those cited in meta-analysis. As our understanding of the COVID-19 continues, the approach and therapeutics are also evolving.